More Scope for Qualitative Economics - Gorman, W. M. (Review of Economic Studies, 1964)
Journal Article More Scope for Qualitative Economics Get access W. M. Gorman W. M. Gorman Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 1, January 1964, Pages 65–68, https://doi.org/10.2307/2295936 Published: 01 January 1964